QUADRATIC POLYNOMIAL OF POWER SUMS AND ALTERNATING POWER SUMS - Leomarich F Casinillo (Journal of Fundamental Mathematics and Applications (JFMA), 2021)
This study aims to construct quadratic polynomials in n for power sums and alternating power sums of consecutive positive integers. In addition, this paper evaluated the said quadratic polynomials under odd and even terms of the series.